The impacts of alternative policy instruments on environmental performance. A firm level study of temporary and persistent effects - Brita Bye; Marit E. Klemetsen (Statistics Norway, Research Department, 2014)
We study the effects of various environmental regulations on environmental performance measured as emission intensity. Moreover, we aim to test whether any such effects are persistent or only temporary. Conventional theory predicts that indirect regulations as opposed to direct regulations provide continuous dynamic incentives for emission reductions. Our unique Norwegian firm level panel data set allow us to identify effects from different types of regulations such as environmental taxes, non-tradable emission quotas and technology standards. The data includes information of different environmental regulations, all kinds of polluting emissions, and a large number of control variables for all polluting incorporated firms. Empirically we identify positive and significant effects from both direct and indirect policy instruments. We also investigate whether the regulations provide continuous dynamic incentives that lead to persistent effects. In contrast to what the literature suggests, we find evidence that direct regulations promote persistent effects. Indirect regulations will, on the other hand, only have potential persistent effects if environmental taxes are increasing over time.
Keywords: C01; C23; D04; D22; H23; L51; Q51; Q58; 330; environmental performance; emission intensity; environmental regulations; command-and-control; environmental taxes; long-run effects